(untitled) (American Journal of Language, Literacy and Learning in STEM Education (2993-2769), 2025)
Issues that lie at the intersection of specializations in linguistics are bounded according to dialectical approach, research object, subject, aim, and methodology. The investigated topics form a coherent whole in terms of theoretical and practical significance, and the priority goal identified by the researcher determines the boundary of the specialization. The determination of the degree of verbal morphological forms in Uzbek is studied as a purely linguistic research, while corpus linguistics acts as a facilitating tool, and methodology serves as a supporting field that implements the results in practice. This topic connects theoretical and applied linguistics, corpus linguistics, and methodology, although in the research process, certain approaches are primary while others play a supporting role.